Noções básicas de infinito e números cardinais - Leão, Alessandro Mignac Carneiro (2014)
In this work, we show basic results about the so-called trans nite numbers and their cardinal arithmetic. For these purpose, we also show some results involving the set theory, as well as equinumerosity, nite sets, in nite sets, countable sets and uncountable sets.